An edition of Fulke Greville's A dedication to Sir Philip Sidney (The life of the renowned Sir Philip Sidney) - Greville, F; Gouws, J; Gouws, J. S. (1976)
﻿ This thesis sets out, firstly, to establish the relationship "between the known representatives of the textandmdash;the editio princeps of 1652 [1652], Trinity College, Cambridge MSS R.7. 32 and 33 [T], Shrewsbury Public Library MS 295 [S], and a manuscript in the possession of Dr. B.E. Juel-Jensen [J]; and, secondly, to provide, as far as is possible, a readable text of the latest state of revision of the work, and a critical apparatus setting out all the passages from the earlier states of the text that were either altered or omitted during the process of revision. The relationship of the four witnesses of the text, established on the basis of irreversible error and alterations that could only have been authorial, may be represented by the following schema, where X, T, and Z stand for three states of revision: [Diagram omitted from transcription] Readings in the present text have been taken from 1652 except where it is thought to be in error. Errors in 1652 have been corrected with readings from T or J and S, depending on where in the transmissional process error was introduced; in a few isolated cases I have emended the text. The accidental characteristics of none of the representatives of the text have been preserved. Spelling, typography and punctuation have all been brought into line with modern conventions, except insofar as this would involve the introduction of historical inaccuracies. The critical apparatus has been constructed so as to allow for an approximate reading of the early state of the text represented by J and S. I have included in the introduction a schematic representation of the transformations to which the work was subjected. This schema will help to locate the material of J and S as it may be found in 1652 and T. In the introduction I have argued that the commonly accepted title of the work should be replaced with that of the Trinity College, Cambridge manuscript: A Dedication to Sir Philip Sidney. This title is not only in accord with Greville's intentions, but it draws attention to the relationship between the work and Greville's other writings. The introduction also includes brief discussions of the literary traditions of the Dedication, of Greville's sources that have been identified, of the period of composition of the text from before March 1610 till the second half of 1614, and of the prose styles employed by Greville. In the notes, particular textual problems only mentioned in the introduction have been considered. I have also been able, in the limited time available to me, to collect about two-thirds of the material necessary for an adequate commentary on the text.